Performance Enhancement of TCP Friendly Rate Control Protocol over Wired networks - N. Ramanjaneya Reddy; Chenna Reddy Pakanati; M. Padmavathamma (International Journal of Electrical and Computer Engineering (IJECE), 2016)
One of the main aims of transport layer protocol is achieving best throughput without any congestion or reduced congestion.  With rapid growing application needs and with increasing number of networks in Internet, there is a primary need to design new protocols to transport layer.  To transmit multimedia applications, one of the suitable congestion control mechanisms in transport layer is TCP Friendly Rate Control Protocol (TFRC).  It controls congestion based on its equation. However, every packet requires an acknowledgement in TFRC. It creates congestion in the network when the transmitted data is very large, which results in reduced throughput. This paper aims to increase the throughput when the transmitted data is large with minimal congestion by reducing the number of acknowledgements in the network.  We modified some fixed parameters in the TFRC equation. The results show the increased throughput with minimal congestion.